Efektivitas Media Dakon Dalam Meningkatkan Kemampuan Pemahaman Matematika Siswa - Risma Anisa Nur Elena; Anggitiyas Sekarinasih (Yayasan Bina Nagari Banyumas, 2026)
This research is motivated by the low ability of students in understanding mathematics on the material of multiplication and division. Students still have difficulty in understanding the basic concepts of multiplication and division operations. This study aims to test the effectiveness of dakon media in improving the mathematical understanding of grade III students of MI Muhammadiyah Toyareka, Purbalingga Regency. This study also assesses the significant difference in effectiveness between classes using dakon media and classes applying conventional methods. This study uses a quantitative method with a quasi-experimental design in the form of a nonequivalent control group design. The results show that dakon media is effective in improving students' mathematical understanding abilities. This is evidenced by the average N-Gain value in the experimental class using dakon media of 0.775 with a percentage of 78% N-Gain score included in the effective category. Meanwhile, the control class using conventional methods obtained an average N-Gain value of 0.192 with a percentage of 19%. In addition, the difference in effectiveness is also supported by the results of the Mann-Whitney U Test on mathematical understanding abilities with a significance value of 0.002. Therefore, it was concluded that dakon media was effective in improving mathematical understanding skills. The difference in effectiveness between the average scores in the experimental and control classes was significant.